Integrating tuberculosis care cascade activities into medical education and training: experiences from a pilot intervention from rural Maharashtra, India - Swathi Krishna Njarekkattuvalappil; Saibal Adhya; Sanjivani Vishwanath Patil; Sanjay Sonyabapu Darade (Frontiers in Public Health)
India has the highest burden of tuberculosis (TB) in the world. The mandatory Family Adoption Programme (FAP) visits to adopted villages by medical college teams is an excellent opportunity to do the ideal “community screening” for TB in a door-to-door manner. We nested an active case finding activity for TB in the FAP visits by MBBS students in rural Pune, Maharashtra and the learnings and recommendations from this pilot intervention are detailed here. It is a sustainable and replicable activity for MBBS students and a great opportunity to collaborate with the national health programme.